PWE-065 Patients' perception of faecal calprotectin testing in inflammatory bowel disease: results from a prospective patient based survey. (17th June 2017) - Kalla, R; Crooks, B; Hall, V; Tatersall, S; Ndlovu, Z; Simon, A; Moriarty, K; Lipscomb, G; Singh, S
Abstract : Introduction: Despite the success of Faecal calprotectin (FC) as a biomarker in Inflammatory Bowel Disease (IBD), there appears to be practical issues with testing in clinical practice, including sample collection, delivery and processing delays. We investigate patients' perception of FC testing in clinical practice. Method: A prospective patient survey was undertaken in a regional IBD unit in England from 12/2016 to 02/2017. Patients completed a 9 point based questionnaire in clinic including diagnosis, patient demographics, previous FC testing, FC testing difficulty rating score (0–4) and preference to alternative methods of disease monitoring including blood tests and endoscopy. Predictors of FC testing difficulty were derived using multivariable logistic regression analysis. Results: A total of 193 patients with IBD completed the survey. There were 112 males with a median age of 48 years (IQR: 36–62). A total of 72 had a diagnosis of CD, 117 UC, and 4 with IBDU patients. Median disease duration was 84 months (IQR 24–180). A total of 110 patients had prior experience of FC testing. Of these, 45% (n=49) rated FC testing either moderately difficult (score 2), difficult (score 3) or very difficult (score 4). The reasons included 'dropping FC sample' (n=7), 'sample collection' (n=28) or 'both' (n=12) and 2 patients did not answer this question. A total of 61%(n=67) patients would rather have a blood test over faecal testing however when given the option of either endoscopy or FC testing, 56%(n=62) patients would prefer non-invasive FC testing, while 29%(n=32) did not have any preference. Multivariable regression analysis identified female gender (Odds ratio(OR):1.92 95% CI:0.85–4.44, AIC:147) and age <49 years (OR: 3.31, CI:1.47–7.77, AIC:153) as predictors of high FC difficulty rating score. A total of 82 patients were FC naïve. If given a choice, 52% patients would prefer blood testing over FC testing and If given the option of either endoscopy or FC testing, 39% patients opted for FC testing while 44% had no preference. In the entire cohort, female gender (OR:1.85, CI:1.03–3.36, AIC:258) and those with disease duration more than 89 months (OR: 1.61, CI:0.90–2.91, AIC: 260) were significantly more likely to opt for blood testing over FC testing. Conclusion: Our study is the first to explore patients' perception of FC testing as a routine biomarker and the practical issues surrounding FC testing. A significant 45% find FC testing challenging, mostly related to sample collection, in particular younger female patients with IBD. Further qualitative studies understanding and addressing these practical issues may aid higher FC uptake in clinic. Disclosure of Interest: None Declared